Learning organisation and job performance among UiTM Perlis staff - Mohd Izwan, Mohd Azman (2015)
The purpose of this study is to investigate the existence of Learning Organisation dimensions in UiTM, specifically in UiTM Perlis and its relationship with Job Performance of the staff, both academic and non-academic. By investigating the effect of the dimension on staff job performance, this study should also determine which dimensions have the most effect on job performance of staff in that campus. 260 respondents were involved in this study. Ultimately, the descriptive analysis result shows that all of the learning organisation dimensions do exist in UiTM Perlis at moderate levels. By using multiple regression analysis, collectively, all seven dimensions are proven to have a positive relationship with job performance of the staff in the campus but individually, it indicates that only three dimensions have a significantly positive relationship with job performance and one with a significantly negative relationship with job performance. The three positively significant dimensions are promote inquiry and dialogue, create systems to capture and share learning, and connect the organisation to its environment. The negatively significant dimension is encourage collaboration and team learning, The three insignificant dimensions are create continuous learning opportunities, empower people toward a collective vision and provide strategic leadership for learning. Using the analysed results, the study discusses the implication of the results and proposes a few recommendations to be considered by the organisation and future researchers.